310 A new proposal for the clinical classification of vulvar lichen sclerosus: an observational prospective study. (4th December 2020) - Boero, Veronica; Liverani, Carlo A; Brambilla, Massimiliano; Monti, Ermelinda; Murina, Filippo; Tozzi, Roberto; Loreto, Eugenia DI; Dell'utri, Chiara Maria F; Libutti, Giada; Parazzini, Fabio
Abstract : Introduction/Background: Vulvar Lichen Sclerosus (VLS) is a chronic inflammatory disorder which commonly affects the female anogenital epithelium, leading to scarring, anatomical distortions, impaired sexual function, decreased quality of life and increased vulvar cancer risk. An agreement to measure VLS severity in a standard way is yet to be defined and, to our knowledge, no standardized clinical classification of anatomical modifications in VLS has been validated. The purpose of this study was to prepare a clinical classification for VLS aimed at defining the morphological patterns of this condition, while stratifying them into grades. The classification is intended to provide a homogeneous and reproducible description of the different features of this disease. It also serves as an important tool for the evaluation of the course of the disease over time, response to treatment, and for comparison of clinical studies. Methodology: A board of seven specialists with expertise in vulvar pathology were asked to outline the anatomical criteria for the definition of VLS severity (phimosis of the clitoris, resorption of the labia minora, involvement of the inter-labial sulcus, and narrowing of the vulvar introitus), identifying five grades to be used to build-up of a score model. The classification was validated by 13 physicians upon pictures of 137 consecutive patients. Each physician individually assigned a grade to each case, according to the abovementioned criteria. Inter-rater agreement among evaluators was analysed by means of ICC (Intraclass Correlation Coefficient). Intra-observer reproducibility and inter-observer concordance in vivo were analysed by means of Kappa index. Results: This study provides a new classification of VLS, based on defined anatomical criteria and graded into mutually exclusive progressive classes (table 1 ). The ICC analysis showed a substantial agreement in the attribution of the grade of VLS among the 137 cases, ICC=0, 89 (0.87–0.91), both in the expert and in the non-expert group (ICC=0.92 and 0.87 respectively). An 'almost perfect' agreement was achieved for intra-observer reproducibility and among physicians in vivo (Kappa 0.93). Conclusion: Our classification showed a high accuracy in defining morphological modifications in VLS. It is easy to use, reproducible, and can be applied by different health care providers in daily clinical practice and in all clinical settings. Disclosure: Nothing to disclose.